Credit Default Swap and Liquidity - Al-Qaisi, Khaldoun Maddallah; Al-Batayneh, Rafat Mohd Soudki (International Journal of Economics and Financial Issues, 2017)
The recent global economic downturn that erupted in the mid 2007 saw an increase of the Credit Default Swaps (CDS) by hundred basis points and severe liquidity crunch in the financial sector of the United States. The recession phase highlighted the importance of the liquidity for the investors and underlined the importance of understanding the connection between the liquidity of the market and the credit markets. In depth, this study tries to understand the relation between the liquidity risk in the CDS market and the credit risk. Along the same line of this study, a study conducted on the different Swiss and German companies revealed that credit risk is not the direct originator of the liquidity risk, but it created by a negative credit shock. In addition, this paper focuses on the causes that intensified the global crisis of (2007) as well as the macro-prudential policies are highlighted that will prevent a similar type of crisis in the future. Keywords: Credit Risk, Liquidity, Financial Crisis. JEL Classifications: G31, G33